Effects of w/b ratio, fly ash, limestone calcined clay, seawater and sea-sand on workability, mechanical properties, drying shrinkage behavior and micro-structural characteristics of concrete. (28th February 2022) - Liu, Jun; An, Ran; Jiang, Zhilu; Jin, Hesong; Zhu, Jihua; Liu, Wei; Huang, Zhenyu; Xing, Feng; Liu, Jiaying; Fan, Xu; Sui, Tongbo
Highlights: The effects of water-binder ratios on slump, mechanical properties and drying shrinkage of SSC were studied. The influence of supplementary cementitious materials (fly ash /LC2) on drying shrinkage of SSC was explored. The relationship between the drying shrinkage and the pore characteristics of SSC was discussed. The micro performance of SSC at different influencing factors was investigated by SEM-EDS, MIP, TGA and XRD. Abstract: There are a large amount of concrete to application in the construction industry in all countries every year, which leads to the consumption of fresh water and river sand increasing. The shortage of fresh water and river sand may lead to the destruction of river ecosystem, especially for coastal regions. Therefore, it is an important approach to study the replacement of fresh water and river sand by seawater and sea sand to improve resources shortage and achieve sustainable development. In this study, eight kinds of concrete were designed by using three different water-binder ratios, two supplementary cementitious materials (SCMs). This study reports the comprehensive results of workability, mechanical strength, drying shrinkage behavior and microstructures of seawater and sea sand concrete (SSC). It has been observed that adding seawater and sea sand can lead to the increase of early compressive strength and the declining of workability, while the utilization of seawater and sea sand can result in the decrease of later strength. With the rising of curing age, SSC with adding SCMs (FA/LC2) has similar or better comprehensive performance than OPC-SSC. The pore structure of SSC is closely related to its drying shrinkage behavior. Scanning electron microscope (SEM) analysis also confirmed that the SSC with mineral admixtures has a more uniform and compact microstructure after long-term curing, and the SSC with 25% LC2 content has the best microstructural property. X-ray diffraction (XRD) and thermogravimetry analysis (TGA) also proved that LC2 system had better chemical reaction performance and higher early activity than FA system. This study can provide an insight into the utilization of seawater and sea sand in concrete and the impact of SCMs on SSC.